Technology Integration in Learning to Read the Al-Qur'an - Tri Bimantoro, Rizal; Alias, Muhamad Firdaus Bin; Syafrianto, Hendra; Abdi, Hamdani; Rahmi, Elvi; K, Munawir (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2024)
This paper explains “Digital Literacy For The Better Generation (DALIBIN): Learning Assistance for the Qur'an and Literacy Empowerment in the Pati District towards Achieving Sustainable Development Goals (SDGs)". This paper is written to review the design of the DALIBIN application, which is designed to meet the community's needs for cross-type digital literacy based on the interpretation of Surah Al-’Alaq verses 1-5. This paper used data obtained from research and development (R&D). Data were collected using the principle of secondary data. The method used in the problem analysis was the qualitative descriptive method. This method was used to describe the design of the DALIBIN digital literacy media app. Based on the problem analysis, it can be concluded that the interpretation of Surah Al-’Alaq verses 1-5 is closely related to the command for humans to seek knowledge and be literate. Thus, the design of the DALIBIN application, which consists of various types of literacy, is expected to improve the quality of people's digital literacy, especially the Qur'anic generation, to step into a future based on renewable technology.